Changing of haemostatic system in a pig model during different types of hypothermic circulatory arrest. (January 2021) - Lei, Li; Xinliang, Guan; Ming, Gong; Xiaolong, Wang; Yuyong, Liu; Yang, Liu; Zining, Wu; Feng, Lan; Haiyang, Li; Hongjia, Zhang
Abstract: Background: Hypothermic circulatory arrest is usually used in aortic surgery, congenital heart defect repairs and other complex surgeries. It is frequently associated with excessive postoperative bleeding and the transfusion of allogeneic blood products. The physiopathology of hypothermic circulatory arrest-induced coagulopathy has never been systematically studied. The aim of the study was to investigate this phenomenon in a pig model. Methods: Ten pigs were randomly assigned to 30 min of hypothermic circulatory arrest at either 15 °C (n = 5) or 25 °C (n = 5). Detection of apoptosis and haemostatic system assays were performed in this experiment. Enzyme-linked immunosorbent assays were performed at ten time points in each group to study the changes in the coagulation system in hypothermic circulatory arrest. All of the statistical analyses were performed in SPSS software, version 18.0, and as bilateral tests, and p < 0.05 was considered statistically significant. Results: There was no significant difference in the effect of different types of hypothermic circulatory arrest on routine laboratory tests and tissue sample analysis (p > 0.05, for all). Our results demonstrated that more severe systemic activation of the coagulation system (TAT and F1+2) was applied in the deep hypothermic circulatory arrest group but not in the moderate hypothermic circulatory arrest group (TAT/p = 0.01, F1+2/p = 0.03). However, this activation of the coagulation system (AT III and PC) was not associated with changes in the anticoagulation pathway (AT III/p = 0.24, PC/p = 0.33). In addition, analysis of biomarkers of the haemostatic system revealed that the consumption of coagulation is more concentrated on extrinsic coagulation factors (FVII/p = 0.01). Conclusions: Moderate hypothermic circulatory arrest is more suitable for patients with coagulation dysfunction. We believe the application of deep hypothermic circulatory arrest should pay more attention to changes in coagulation rather than the anticoagulation pathway. Extrinsic coagulation factor supplementation is more effective after deep hypothermic circulatory arrest. Highlights: The effect of HCA at different types on liver was no obvious different. MHCA is more suitable for patients with coagulation dysfunction. During DHCA, we should focus on coagulation rather than anticoagulation pathway. Extrinsic coagulation factors supplementation is more effective after DHCA.